Combined ibrutinib and venetoclax for treatment of patients with ibrutinib‐resistant or double‐refractory chronic lymphocytic leukaemia. (16th July 2022) - Hampel, Paul J.; Rabe, Kari G.; Call, Timothy G.; Ding, Wei; Leis, Jose F.; Kenderian, Saad S.; Muchtar, Eli; Wang, Yucai; Koehler, Amber B.; Parrondo, Ricardo; Schwager, Susan M.; Shi, Min; et al.
Summary: Patients with chronic lymphocytic leukaemia (CLL) disease progression on ibrutinib or after sequential ibrutinib and venetoclax‐based treatments (double‐refractory) have poor outcomes. In this retrospective study, we analysed outcomes with combined ibrutinib and venetoclax treatment in these groups of patients. The median treatment‐free and overall survival for 22 patients with prior progression on ibrutinib (venetoclax‐naïve) were 23.7 and 47.1 months respectively. In 11 patients with double‐refractory CLL, the median treatment‐free and overall survival were 11.2 and 27.0 months respectively. The combination of ibrutinib and venetoclax may help bridge the current gap in options for patients with disease refractory to the most commonly used novel agents.